An Assessment of Microplastics (MPs) Sedimentary Accumulation in Seagrass Meadows of Mare Island Conservation Area, North Maluku, Indonesia - Yunita Ramili; Halikuddin Umasangaji (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2022)
Research on the occurrence and the characteristics of microplastics (MPs) sedimentary in seagrass meadows at the area of Mare Island conservation is the very first study in this region. The objectives of this work is to determine the abundance and the characteristics of MPS and its diversity in the two villages namely Maregam and Marekofo at the Island. Samples are collected using sediment core, then dried and extracted using NaCl to separate the density. MPs were identified under a microscope after going through the filtering process. The abundance of MPs particles ranges from 17,000 - 37,000 particles. kg-1dry weight (dw) sediment at Station 1 (Maregam) and 13.839 - 30,666 particles.kg-1 dw sediment at Station 2 (Marekofo). In general, the average value of MPs abundance at station 1 higher than station 2 were 27.090 ± 13.908 particles.kg-1 dw of sediment and 18,368 ± 10,625 particles.kg-1 dw of sediment, respectively. Statistically there no significance difference of the MPs abundance between the two station Furthermore, the predominance of MPs types were fiber and fragments, while the majority of colors of particles were blue. While the results of the microplastic diversity test indicated that MPS particles at Mare Island were not too complex and were in unstable conditions. Even though the less density of the population at the island, MPs were quite high compared to other areas in the world. This finding is allegedly that those MPs were supplied from the distance which transmitted by hydro-oceanographic and meteorology factors, beyond of local contribution.Keywords: Microplastic, seagrass bed, sediment, conservation area, Mare Island